MDCM, Inc. (A) : IT strategy synchronization - Jeffery, Mark, 1965- (SAGE Knowledge. Cases., 2006)
The case examines the issues of formulating a set of IT objectives aligned with corporate strategy. Specifically, the case describes a firm that has grown rapidly through acquisitions. As a result of these acquisitions, the new conglomerate is not responsive to the competitive environment. The firm has therefore launched a new transformation strategy called Horizon 2000, but it has yet to develop a corresponding IT strategy. Students are then expected to develop an executive-level IT strategy for the firm.